Biochemical Traits, Survival and Biological Properties of the Probiotic Lactobacillus plantarum Grown in the Presence of Prebiotic Inulin and Pectin as Energy Source - Raffaele Coppola; Filomena Nazzaro; Florinda Fratianni; Pierangelo Orlando (MDPI AG, 2012)
The viability of the probiotic strain Lactobacillus plantarum subsp. plantarum, after its passage through simulated gastric and pancreatic juices, was evaluated as function of its pre-growth in a medium containing the known prebiotics pectin or inulin, and was compared to glucose used as control. The presence of pectin or inulin did not markedly affect the growth (10.07 log10 colony forming units/mL and 10.28 log10 colony forming units/mL for pectin and inulin respectively versus 10.42 log10 colony forming units/mL obtained for glucose). Pectin and inulin, in contrast to glucose, induced cell stress resistance against gastrointestinal juices (D log101.5 and 2.4 colony forming units/mL respectively, versus D log10 4.0 for glucose). The data were corroborated by the analysis of the protein pattern following stress treatments which, in the case of microbial cells grown with glucose, revealed a more marked protein degradation after the double passage through simulated gastric and intestinal juices. Inulin stimulated the production of the relevant healthy bio-molecule butyrate, which amount was 30% higher respect of growth in the presence of glucose. Inulin and pectin improved cell DPPH scavenging activity, and an impressive hydrophobicity (35.28% and 34.81%, respectively) was observed with respect to the microbial growth in presence of glucose (3.39%).